Պետականակենտրոն և դավանակենտրոն արժեքային համակարգեր - Սարգսյան, Աշոտ
For the study of Armenian political thought, it is important to know on what value systems was it based. Research in historiography leads to the following conclusions. There were two value systems in the 5th-century Armenia: state-centric and religio-centric. The first goes back to the traditions of the 600-year statehood and is reflected in Movsēs Khorenatsi‘s History of Armenia, while the second, shaped on the basis of the new religion, Christianity, is reflected in other historiographic works of the same and later centuries. Для изучения армянской политической мысли важно, какие системы ценностей легли в ее основу. Изучение историографических памятников приводит к следующему заключению. В V веке в Армении присутствовали две системы ценностей: государственно-центричная и веро-центричная. Первая восходит к традицям 600летней государственности и отражена в Истории Армении Мовсеса Хоренаци. Вторая образовалась на основе новой религии, христианства, и отражена в трудах других историографов V и последующих веков.
Keywords: Պատմություն; Ազգագրություն